Evidence of an ice-dammed lake outburst in the North Sea during the last deglaciation - Hjelstuen, Berit Oline; Sejrup, Hans Petter; Valvik, Espen; Becker, Lukas W. M. (Marine Geology, 2018)
Recent reconstructions suggest that the British-Irish and Fennoscandian ice sheets coalesced and covered the central and northern North Sea from ca. 26 cal. ka BP and until ca. 19 cal. ka BP. At ca. 19 cal. ka BP the Norwegian Channel Ice Stream started to retreat and the ice sheets broke apart at ca. 18.7 cal. ka BP. This led to a drainage of an ice-dammed lake in the southern North Sea northwards via the Norwegian Channel into the SE Nordic Seas. In this paper we combine information from high resolution TOPAS profiles, bathymetric records and shallow borings to study the ice-dammed lake outburst, a common deglaciation process but which rarely has been evidenced in such a detail from the marine realm. A 12 m deep and 3 km wide incision at the northeastern part of the Dogger Bank is suggested to represent the point where the ice-dammed lake breached. The glacial lake outburst flood, which had an estimated peak discharge of 9.8 x 10(4)-2.9 x 10(5) m(3)/s and lasted for about 5-15 months, flowed between the withdrawing British-Irish and Fennoscandian ice sheets following the crest of the Ling Bank northwards. Along this path, about 300 km downstream of the break-through point, an up to 10 m thick sediment package with a prograding-aggrading sedimentation pattern, typical for ice-dammed lake outburst deposits, has been deposited. This sediment package was deposited in a high-energy environment, immediately following extensive erosion of the underlying till unit of Last Glacial Maximum age. An oxygen isotope anomaly and an associated ultra-rapidly deposited meltwater plume on the Norwegian continental margin, dated to ca. 18.7 cal. ka BP, also witness this lake outburst. The ice-dammed lake outburst flood occurred when evidence suggest a sea level at least 110 m lower than at present in the region. As the sea level rose, following the melting of the Last Glacial Maximum ice sheet, the Ling Bank Delta developed on top the outburst deposits. The delta, indicating a sea level close to 80 m below present, has an extent ...